2007
DOI: 10.1523/jneurosci.2571-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Shape Abnormalities in Individuals with Schizophrenia and Their Nonpsychotic Siblings

Abstract: Deficits in the volume of the thalamus have been observed in both individuals with schizophrenia and their nonpsychotic relatives. However, no studies to date have examined the underlying pattern of thalamic shape change in relatives of individuals with schizophrenia. This study examined the volume and shape of the thalamus in schizophrenia subjects, their siblings, and healthy control individuals. T1-weighted magnetic resonance scans were collected in a group of young subjects with schizophrenia (mean age, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
98
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 53 publications
(64 reference statements)
13
98
0
1
Order By: Relevance
“…The canonical analysis was designed to score the SCZ-SIB and CON-SIB along the dimension that "maximized" the difference between SCZ and CON. Thus, the canonical weighting coefficients were obtained from the contrast between SCZ and CON (33). A canonical score was obtained for each structure and subject by applying these weighting coefficients to the original dependent variables (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The canonical analysis was designed to score the SCZ-SIB and CON-SIB along the dimension that "maximized" the difference between SCZ and CON. Thus, the canonical weighting coefficients were obtained from the contrast between SCZ and CON (33). A canonical score was obtained for each structure and subject by applying these weighting coefficients to the original dependent variables (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…From an initial group of 216 potential subjects that fit inclusion criteria (see below), the final group of study subjects were selected from those who had an MR scan of acceptable quality and whose sibling also completed MR scanning. This cohort of subjects was the same as that used in our previous report on the thalamus (33).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the subcortical level, it was not until the advent of shape analysis techniques (e.g., Patenaude et al 2011) that successfully estimating regional shape variations in subcortical structures with high anatomical precision was possible. This approach has been mainly applied to unveil abnormal subcortical morphology in mental disorders or disease (Coscia et al 2009;Harms et al 2007;Kang et al 2008;McKeown et al 2008;Qiu et al 2008;Xu et al 2008) but recently also to understand the role of subcortical shape in high-order cognition in healthy populations (Burgaleta et al 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in the medio-dorsal, pulvinar, and centromedian nuclei of the thalamus, all connected to the lateral prefrontal cortex (LPFC), a site of well-documented abnormalities in schizophrenia (Weinberger et al, 2001), have been reported with several methods (eg, Andrews et al, 2006;Byne et al, 2002;Byne et al, 2007;Harms et al, 2007;Hazlett et al, 1999;Kemether et al, 2003;Kessler et al, 2009;Kumari et al, 2010;Lehrer et al, 2005;Popken et al, 2000;Rose et al, 2006, but see, for example, Danos et al, 2005;Dorph-Petersen et al, 2004;Kreczmanski et al, 2007 for negative findings). Some functional MRI (fMRI) studies found abnormalities in the correlation between the activity in the thalamus and the PFC in schizophrenia (eg, Meda et al, 2010;Schlosser et al, 2003;Welsh et al, 2010;Zhou et al, 2007), which may reflect alterations in anatomical connectivity.…”
Section: Introductionmentioning
confidence: 99%